2019
DOI: 10.1038/s41377-019-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for designing orangish-red-emitting phosphor via oxygen-vacancy-induced electronic localization

Abstract: Phosphor-converted white-light-emitting diodes (pc-WLED) have been extensively employed as solid-state lighting sources, which have a very important role in people’s daily lives. However, due to the scarcity of the red component, it is difficult to realize warm white light efficiently. Hence, red-emitting phosphors are urgently required for improving the illumination quality. In this work, we develop a novel orangish-red La4GeO8:Bi3+ phosphor, the emission peak of which is located at 600 nm under near-ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
131
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 295 publications
(133 citation statements)
references
References 34 publications
1
131
1
Order By: Relevance
“…As for the Eu 2+ , Ce 3+ , and Mn 2+ ions, however, one major drawback is the evitable light re-absorption problem in the visible spectral region. Over the past years, a number of works had pointed out the necessity of solving this problem [22,[30][31][32][33][34][35][36][37], but it seems that the d-f (i.e., for Eu 2+ , and Ce 3+ ) and 4…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the Eu 2+ , Ce 3+ , and Mn 2+ ions, however, one major drawback is the evitable light re-absorption problem in the visible spectral region. Over the past years, a number of works had pointed out the necessity of solving this problem [22,[30][31][32][33][34][35][36][37], but it seems that the d-f (i.e., for Eu 2+ , and Ce 3+ ) and 4…”
Section: Introductionmentioning
confidence: 99%
“…., for Mn 2+ ) transitions feature an inherently-inviolable law, making them impossible to have the tunable-emission and non-visible re-absorption at the same time. By contrast, a dopant like Bi 3+ ion could be relevant to address well this point [22,32,[35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the DRS can be in accordance with the excitation spectrum of 0.10 Ce 3+ doped CGHAO. The band gap ( E g ) of CGHAO can be obtained by the following equations: 31‐32 [Ffalse(Rfalse)hυ]2=Afalse(hυEgfalse),Ffalse(Rfalse)=false(1Rfalse)22R,where R refers to the obtained reflection in DRS, and F ( R ) and A are the Kubella‐Munk function and constant, respectively, while the incident photo energy is substituted by hυ . As shown in the right bottom corner inset of Figure 4, by making tangent to F ( R ) = 0, the obtained value of CGHAO band gap is approximately 5.56 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Li et al reported a new method that oxygen vacancy can induce energy level splitting of Bi 3+ ion to achieve long-wavelength emission. 7 In this work, from the viewpoint of crystal structure, we successfully realized the long-wavelength emission of Bi 3+ ions under NUV excitation. The proposed phosphor presents one-dimensional chain structure of cations along a certain crystal direction, as a result, creating abundant oxygen vacancies during high temperature sintering.…”
Section: Introductionmentioning
confidence: 99%